2007
DOI: 10.1007/s10388-007-0113-0
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-colony stimulating factor-producing esophageal carcinosarcoma: a case report

Abstract: An 80-year-old man presented at our hospital with chest oppression and vomiting. An endoscopic examination revealed a tumor in the lower portion of the esophagus, and the patient was diagnosed as possibly having esophageal carcinosarcoma based on a histological examination of endoscopic biopsy specimens. During the initial medical examination, the patient had a high leukocyte count and a high level of serum granulocyte-colony stimulating factor (G-CSF). Moreover, immunohistochemical examination revealed cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Some authors have previously reported G-CSF-producing carcinosarcoma of the esophagus [13][14][15]. However, to the best of our knowledge, only fi ve cases of G-CSF-producing esophageal SCC without a sarcoma component have been described in the English literature [8][9][10][11], including our present case ( Table 1).…”
Section: Discussionmentioning
confidence: 57%
“…Some authors have previously reported G-CSF-producing carcinosarcoma of the esophagus [13][14][15]. However, to the best of our knowledge, only fi ve cases of G-CSF-producing esophageal SCC without a sarcoma component have been described in the English literature [8][9][10][11], including our present case ( Table 1).…”
Section: Discussionmentioning
confidence: 57%
“…Most of these cases have been reports of lung cancer, and esophageal cancers producing G-CSF are quite rare. Esophageal carcinosarcomas with G-CSF production have been reported in only 11 cases, including the present case (Table 1) [10][11][12][13][14][15][16][17][18][19]. According to Asano et al, the diagnostic criteria for G-CSF-producing tumors include (1) marked leukocytosis, (2) high serum concentration of G-CSF, (3) normalization of leukocyte count after tumor resection, and (4) evidence of G-CSF production in tumor cells [5].…”
Section: Discussionmentioning
confidence: 94%
“…Early detection and treatment are important in curing G-CSF-producing tumors because there is no specifi c approach for treating esophageal carcinosarcoma with G-CSF production at the present time [18,19]. In addition, the treatment of patients with carcinomas that are able to produce G-CSF requires special care when it includes the management of G-CSF for bone marrow recovery after chemotherapy and/or radiotherapy of cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A G-CSF-producing carcinosarcoma of the esophagus has been reported in only 11 cases from 1997 to 2008 [1,5,[7][8][9][10][11][12][13][14][15]. According to Asano et al [16], the diagnostic criteria for G-CSF-producing tumors are: (1) high serum concentration of G-CSF, (2) marked leukocytosis, (3) decrease in leukocyte count after tumor removal, and (4) positive staining for G-CSF in tumor cells.…”
Section: Discussionmentioning
confidence: 99%